2019
DOI: 10.1140/epjc/s10052-019-7032-9
|View full text |Cite
|
Sign up to set email alerts
|

Covariant holographic entanglement negativity for disjoint intervals in $$AdS_3/CFT_2$$

Abstract: We advance a construction for the covariant holographic entanglement negativity for time dependent mixed states of disjoint intervals in (1 + 1) dimensional conformal field theories (C FT 1+1) dual to bulk non static Ad S 3 geometries. Application of our proposal to such mixed states in a C FT 1+1 dual to bulk non extremal and extremal rotating BTZ black holes exactly reproduces the replica technique results in the large central charge limit. We also investigate the time dependent holographic entanglement nega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 49 publications
14
62
0
Order By: Relevance
“…In a recent article [53], the authors computed the gravitational path integral corresponding to the Renyi negativities in holographic theories and demonstrated that it is dominated by a bulk replica symmetry breaking saddle. Following this in [48], the authors of the present article demonstrated that for two dimensional holographic C F T s and for the case of subsystems involving spherical entangling surfaces in higher dimensions, the computation in [53] also serves as a proof of the holographic proposals [40,43,45].…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…In a recent article [53], the authors computed the gravitational path integral corresponding to the Renyi negativities in holographic theories and demonstrated that it is dominated by a bulk replica symmetry breaking saddle. Following this in [48], the authors of the present article demonstrated that for two dimensional holographic C F T s and for the case of subsystems involving spherical entangling surfaces in higher dimensions, the computation in [53] also serves as a proof of the holographic proposals [40,43,45].…”
Section: Introductionsupporting
confidence: 53%
“…We then briefly describe the entanglement negativity of a bipartite system in a random mixed state and the corresponding Page curve derived using the random matrix techniques in [70]. Subsequently, we discuss the holographic entanglement negativity proposal for various mixed state configurations in the AdS 3 /CFT 2 scenario conjectured in [40,43,45].…”
Section: Review Of the Earlier Resultsmentioning
confidence: 99%
See 3 more Smart Citations